Effect of glatiramer acetate on short‐term memory impairment induced by lipopolysaccharide in male mice. (8th June 2016) - Mohammadi, Fatemeh; Rahimian, Reza; Fakhraei, Nahid; Rezayat, Seyed Mahdi; Javadi‐Paydar, Mehrak; Dehpour, Ahmad R.; Afshari, Khashayar; Ejtemaei Mehr, Shahram
Abstract: Glatiramer acetate (GA) demonstrates neuroprotective, neurogenesis, and anti‐inflammatory properties. This study examines the probable protective effect of acute GA on lipopolysaccharide (LPS)‐induced memory impairment in male mice and further explores which routes of administration [subcutaneous (s.c.) or intracerebroventricular (i.c.v.)] exert optimum effect. Memory performance was evaluated in two‐trial recognition Y‐maze and passive‐avoidance tasks evaluating special recognition memory and fear memory, respectively. Memory impairment was induced by LPS [100 μg/kg, intraperitoneally (i.p.)], 4 h before training. In Y‐maze, GA (10, 2.5, 0.625, 0.153, and 0.03 mg/kg, s.c.; 250 μg/mouse; i.c.v.) was administered 10 min following LPS, and special memory was assayed in Y‐maze apparatus. In passive avoidance, LPS (100, 250 μg/kg; i.p.) was injected 4 h before receiving foot shock, and GA (10, 2.5; s.c.) or (250 μg/mouse; i.c.v.) was administered 4 h before the shock. Following 24 h, the fear memory was evaluated. Memory impaired significantly following LPS (100, 250 μg/kg; i.p.) in Y‐maze and passive‐avoidance tasks, P < 0.001 and P < 0.05, respectively. The data revealed that GA (250 μg/mouse, i.c.v.) and GA (10, 2.5 mg/kg; s.c.) in Y‐maze reversed memory impairment (LPS 100 μg/kg, i.p.) ( P < 0.01). In passive‐avoidance task, GA (2.5, 10 mg/kg; s.c.) reversed LPS‐induced impairment and the mice showed significantly longer latency times during the retention trial ( P < 0.01). GA improved memory impairment both centrally and systemically. It improved spatial recognition memory increasing the average time in the novel arm and improved fear memory increasing latency time. GA administration improved memory impairment profoundly through both systemic and central routs.